Answer:
y=1/3x-3
Step-by-step explanation:
use the eqation y-y1 = m(x-x1)
plug in slop as m and points as x and y
so now you have --> y-(-4)=1/3(x-(-3))
two negatives = a positive --> y+4=1/3(x+3)
distribute the 1/3 --> y+4= 1/3x + 1
subtract 4 from both sides --> y= 1/3x - 3
She should have to pay $380.25 in interest for the jet ski.
Answer:
so whats the question?
Step-by-step explanation:
Step 1. Convert 3 1/3 to improper fraction.
- 3 * 3 + 1/3 ÷ 9
Step 2. Simplify 3 * 3 to 9
-9 + 1/3 ÷ 9
Step 3. Simplify 9 + 1 to 10
-10/3 ÷ 9
Step 4. Use this rule: a ÷ b/c = a * c/b
-10/3 * 1/9
Step 5. Use this rule: a/b * c/d = ac/bd
-10 * 1/3 * 9
Step 6. Simplify 10 * 1 to 10
-10/3 * 9
Step 7. Simplify 3 * 9 to 27
-10/27
Galaxy B has more stars. When expanded, Galaxy A has 50,000,000 stars, while Galaxy B has 20,000,000,000 stars. Galaxy A has 2.5*10⁻³ times as many stars as Galaxy B. Galaxy B has 4*10² times as many stars as Galaxy A.